Analysis of The Influence of Principal Leadership and Emotional Intelligence on Teacher Motivation and Performance - Mandela, Erna; Hendra, Robi; Habibi, Akhmad (Jurnal Paedagogy, 2026)
This study examines the influence of principal leadership and emotional intelligence on teachers’ work motivation and performance. Employing a quantitative explanatory method, the research involved a sample of 220 senior high school teachers in Sarolangun Regency. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The results indicate that principal leadership (β = 0.505) and teachers’ emotional intelligence (β = 0.404) have significant positive effects on work motivation. Both variables also exert direct positive effects on teacher performance. Notably, work motivation emerges as the strongest predictor of performance (β = 0.706) and serves as a key mediating variable that strengthens the indirect effects of leadership and emotional intelligence on performance. These findings suggest that improving teacher performance requires strategies that extend beyond enhancing leadership practices and emotional competencies to include the systematic cultivation of intrinsic motivation. Accordingly, this study recommends that teacher development policies integrate emotional intelligence and transformational leadership training to foster a school climate that supports optimal teacher motivation and performance.